Electrospun carbon nanofibers coated with urchin-like ZnCo2O4 nanosheets as a flexible electrode material. Issue 16 (1st April 2016) - Chen, Hua; Jiang, Guohua; Yu, Weijiang; Liu, Depeng; Liu, Yongkun; Li, Lei; Huang, Qin; Tong, Zaizai
Abstract : Electrospun carbon nanofiber composites (ZnCo2 O4 /Ag–GO–CNFs) coated with 3D urchin-like ZnCo2 O4 nanosheets have been prepared and exhibit excellent specific capacity and cycling stability. Abstract : Electrospun carbon nanofiber composites (ZnCo2 O4 /Ag–GO–CNFs) coated with 3D urchin-like ZnCo2 O4 nanosheets to form a shish-kebab structure have been prepared using a combination of electrospinning, carbonization and hydrothermal treatments. The composition and microstructure of ZnCo2 O4 /Ag–GO–CNFs were investigated using field emission scanning electron microscopy (FE-SEM), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), X-ray diffraction (XRD) and Brunauer–Emmett–Teller (BET) analysis. Interestingly, ZnCo2 O4 /Ag–GO–CNFs provided a new style of electrode materials and exhibited an excellent specific capacity of 459.48 mA h g −1 at 20 mV s −1 . Notably, the specific capacity of ZnCo2 O4 /Ag–GO–CNFs also exhibited a remarkable cycling stability (96.0% retention after 9000 cycles), which holds great promise for practical applications in energy storage devices as a carbon-based electrode material.